2017
DOI: 10.1007/s00216-017-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Feruloyl dopamine-O-hexosides are efficient marker compounds as orthogonal validation for authentication of black cohosh (Actaea racemosa)—an UHPLC-HRAM-MS chemometrics study

Abstract: Due to the complexity and variation of the chemical constituents in authentic black cohosh (Actaea racemosa) and its potential adulterant species, an accurate and feasible method for black cohosh authentication is not easy. A high resolution accurate mass (HRAM) LC-MS fingerprinting method combined with chemometric approach was employed to discover new marker compounds. Seven hydroxycinnamic acid amide (HCAA) glycosides are proposed as potential marker compounds for differentiation of black cohosh from related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…It is assumed that its main function in plants is to strengthen the cell walls and therefore prevent the entry of pathogens into suberizing tissue. The biosynthesis of hydroxycinnamoyl amides has been well studied, but a UGT capable of glucosylating phytoalexins has not been reported to date, although glucosides of the amides have been frequently found (Yahagi et al ., ; Bolleddula et al ., ; Nikolić et al ., , ; Yang et al ., ; Yim et al ., ; Zhang et al ., ; Pei et al ., ; Geng et al ., ; Oliveira de Silva and Batista, ; Wang et al ., ). The biological function of glucosides of hydroxycinnamoyl amides is unclear but they might play a similar role like monolignol glucosides in plant defence (Le Roy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that its main function in plants is to strengthen the cell walls and therefore prevent the entry of pathogens into suberizing tissue. The biosynthesis of hydroxycinnamoyl amides has been well studied, but a UGT capable of glucosylating phytoalexins has not been reported to date, although glucosides of the amides have been frequently found (Yahagi et al ., ; Bolleddula et al ., ; Nikolić et al ., , ; Yang et al ., ; Yim et al ., ; Zhang et al ., ; Pei et al ., ; Geng et al ., ; Oliveira de Silva and Batista, ; Wang et al ., ). The biological function of glucosides of hydroxycinnamoyl amides is unclear but they might play a similar role like monolignol glucosides in plant defence (Le Roy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, testing botanical natural products for adulteration is critical. Several research groups have used targeted 64,87,90,[111][112][113] or untargeted methods [114][115][116] to identify adulterants in botanical natural products. For example, we studied 35 commercial products listed as "goldenseal".…”
Section: Adulteration Of Botanical Natural Productsmentioning
confidence: 99%
“…Untargeted metabolomics may serve as a useful tool for identifying unexpected contaminants. 29,111,115,127 However, it should be noted that untargeted methods are likely to have higher limits of detection than targeted methods; thus, the former may fail to detect low-level contaminants. Furthermore, some contaminants are detectable only with specialized analytical methods.…”
Section: Consideration Of Contaminationmentioning
confidence: 99%
“…Though several targeted techniques have been used to find adulterants in dietary supplements [Simmler, 2017; Steuer, 2017], there has not yet been a study performed to detect adulteration in a sample set of commercial products, ostensibly derived from the same botanical, with an untargeted approach. Untargeted metabolomics approaches have been employed to discriminate between different botanical species as well as variations in the geographic origin of materials [Kang, 2008; Mncwangi, 2014], and studies adulterating pure botanical material have shown discriminating patterns that can be discerned using untargeted techniques [Dowlatabadi, 2017; Geng, 2015; Geng, 2017]. However, little attention has been paid to commercial botanical products, where neither the geographical provenance, cultivation conditions, nor the harvesting and production specifications are known.…”
Section: Introductionmentioning
confidence: 99%